1999
DOI: 10.1109/34.790425
|View full text |Cite
|
Sign up to set email alerts
|

Super-resolution reconstruction of image sequences

Abstract: ÐIn an earlier work, we have introduced the problem of reconstructing a super-resolution image sequence from a given low resolution sequence. We proposed two iterative algorithms, the R-SD and the R-LMS, to generate the desired image sequence. These algorithms assume the knowledge of the blur, the down-sampling, the sequences motion, and the measurements noise characteristics, and apply a sequential reconstruction process. It has been shown that the computational complexity of these two algorithms makes both o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
134
4
11

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(150 citation statements)
references
References 12 publications
0
134
4
11
Order By: Relevance
“…We review the method introduced previously (Farsiu et al, 2004b), which offers an extremely efficient recursive algorithm for dynamic Super-Resolution. Although such a recursive solution for Super-Resolution has been addressed before (Elad and Feuer, 1999), we now show the speedups applicable for the case of translational motion and common space-invariant blur. This simplified model empowers us to use the two step algorithm that was described in Section IV.A for solving the dynamic case.…”
Section: ) Orientation Regularizationmentioning
confidence: 99%
See 2 more Smart Citations
“…We review the method introduced previously (Farsiu et al, 2004b), which offers an extremely efficient recursive algorithm for dynamic Super-Resolution. Although such a recursive solution for Super-Resolution has been addressed before (Elad and Feuer, 1999), we now show the speedups applicable for the case of translational motion and common space-invariant blur. This simplified model empowers us to use the two step algorithm that was described in Section IV.A for solving the dynamic case.…”
Section: ) Orientation Regularizationmentioning
confidence: 99%
“…Note that in order to consider the varying reliability of measurements gathered at each location, the weighting can also be applied on a pixel-bypixel basis [(Farsiu et al, 2004b)]. We use the L 2 norm to follow Elad and Feuer's (1999) model (a robust data fusion term using L 1 norm minimization is part of our ongoing work).…”
Section: ) Orientation Regularizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although work has been devoted to the problem of reconstruction of one high resolution image from a sequence of low resolution ones (see for instance [1][2][3][4][5] and [6] for a review), not much work has been reported on the problem of increasing the resolution of a whole image sequence simultaneously (see however [7][8][9]). …”
Section: Introductionmentioning
confidence: 99%
“…A number of superresolution techniques have been proposed in recent years [1][2] [3][5] [6] [7][9] [10]. They can be categorized into two representative approaches: the first is to produce a superresolution image from a set of low-resolution ones based on learning [5] [7][10]; another approach is to model the texture as a Markov Random Field (MRF) [3][6] [7]. These methods are mainly applied to generic images.…”
Section: Introductionmentioning
confidence: 99%